Kazakhstan’s Bolashak Scholarship Program - Sagintayeva, Aida; Jumakulov, Zakir (International Higher Education, 2015)
Government sponsored study abroad programs are one approach to developing the human capital of a country. From our review of the characteristics and outcomes of one long-standing government-sponsored international scholarship program (Kazakhstan’s Bolashak program), we identify five lessons: 1) align the program to countries’ strategic economic development needs, 2) maximize the benefit through the selection of quality destination institutions, 3) ensure transparency, 4) align the economic needs to the level of study programs, and 5) provide incentives for scholarship recipients to return to the home country.